Migrants: First work encounters - van Tonder, Chris; Soontiens, Werner (Elsevier BV, 2013)
Migrants struggle to perform to expectation during their early years of settlement – a phenomenon usually ascribed to a combination of host country characteristics, migrant profile and the ‘acculturation’ process. The current study aimed to explore the role of migrants’ ‘first work encounters’ against the background of acculturation. Semi-structured phenomenological interviews were conducted with 19 South African migrants to Australia. Apart from confirming the personally challenging nature of migration, the study revealed that first work encounters facilitate realism, induce culture shock and generally influence migrants’ adjustment and acculturation. The findings have important implications for migrant support and Human Resource Management practices.